Heavy Metal Contamination in Pond, Tube Well and Tap Water of Mymensingh Town - Auyon, S T; Usha, K F; Islam, M A; Khan, M B; Farukh, M A (Journal of Environmental Science and Natural Resources, 2025)
Heavy metals are highly toxic, persistent, and accumulative, making them significant environmental pollutants. This study aimed to assess the heavy metal content in pond, tube well, and tap water from five locations in Mymensingh Sadar. A total of 15 composite water samples were collected from the Bangladesh Agricultural University (BAU) campus, Bridge Moor, Maskanda, Town Hall, and Ganginar Par and analyzed using Inductively Coupled Plasma Mass Spectrometry (ICP-MS) following standard methods. The results were compared with WHO drinking water standards. In pond water, arsenic (As), cadmium (Cd), cobalt (Co), lead (Pb), chromium (Cr), nickel (Ni), copper (Cu), iron (Fe), manganese (Mn), and zinc (Zn) were detected across all sites, except Cr in Maskanda, BAU campus, and Town Hall, and Ni in Bridge Moor and Ganginar Par. Pb exceeded the WHO limit (11.6 ppb) in Town Hall pond water. In tube well water, Fe (500.5 ppb) and Mn (165 ppb) surpassed WHO limits in Ganginar Par and BAU campus, respectively, while other metals remained within safe levels. In tap water, Fe (448.8 ppb) in Ganginar Par and Mn (129.8 ppb) in Bridge Moor exceeded WHO limits. Cr was found only in Ganginar Par tap water, while BAU tap water contained no Ni. However, Town Hall tap water had the highest Ni concentration (7.7 ppb). Given the elevated levels of certain heavy metals, purification measures should be prioritized before using the contaminated water for drinking purposes. Environ. Sci. & Natural Resources, 14(1&2): 16-19, 2025